2020
DOI: 10.1128/jvi.01441-19
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Produces Discrete Small Noncoding RNAs Independently of the Host MicroRNA Pathway Which Lack RNA Interference Activity in Bat and Human Cells

Abstract: The question as to whether RNA viruses produce bona fide microRNAs (miRNAs) during infection has been the focus of intense research and debate. Recently, several groups using computational prediction methods have independently reported possible miRNA candidates produced by Ebola virus (EBOV). Additionally, efforts to detect these predicted RNA products in samples from infected animals and humans have produced positive results. However, these studies and their conclusions are predicated on the assumption that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 123 publications
2
18
0
Order By: Relevance
“…À 160 pg/ ml, 7-11 y.o. À 100-110 pg/ml, [11][12][13][14][15] 3 pg/ml. The age-related changes in melatonin levels were observed during the nightly production of melatonin only.…”
Section: Elderly Have Reduced Level Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…À 160 pg/ ml, 7-11 y.o. À 100-110 pg/ml, [11][12][13][14][15] 3 pg/ml. The age-related changes in melatonin levels were observed during the nightly production of melatonin only.…”
Section: Elderly Have Reduced Level Of Melatoninmentioning
confidence: 99%
“…The origins of bats' coronaviruses and factors of viral pathogenesis [9][10][11] are only partially understood. Mechanisms of anti-viral resistance in bats are understood even less, remaining mostly on the level of hypothesis [8,12,13]. SARS-CoV-2 is 96% identical to another bat's coronavirus Bat-SARSr-CoV RaTG13 [14].…”
Section: Bats Have Higher Levels Of Melatonin Than Humansmentioning
confidence: 99%
“…The origins of bats' coronaviruses and factors of viral pathogenesis [9,10,11] are only partially understood. Mechanisms of anti-viral resistance in bats are understood even less, remaining mostly on the level of hypothesis [12,13,14]. SARS-CoV-2 is 96% identical to another bat's coronavirus Bat-SARSr-CoV RaTG13 [15].…”
Section: Bats Have Higher Levels Of Melatonin Than Humansmentioning
confidence: 99%
“…Results obtained in the studies conducted after 2003 SARS and 2014 Ebola virus outbreaks showed that viral small non-coding RNA molecules are involved in pathogenesis of the disease ( Morales et al, 2017 ; Prasad et al, 2019 ; Teng et al, 2015 ). Discovering these RNA molecules may help to understand virus-host interactions during infection that could speed up effective treatment of SARS-CoV-2 caused COVID-19.…”
Section: Introductionmentioning
confidence: 99%